Application of Growth Models to Human Computer Interaction (hci) Research Literature - Kumar, Suresh (Journal of Information and Knowledge, 2014)
The study explores the applicability of three models namely exponential model, logistic model and power model on HCI research literature of world and top twenty nations, as reflected in Science Citation Index-Expanded for a period of 25 years, from 1987 to 2011. The criteria for selection of growth models are based on two growth rate functions suggested by Egghe and Rao. This methodology is found satisfactory, except for data series where there is no clear trend observed in second growth rate function. The analysis suggests that growth of all the 21 data set is explained by both logistic growth model and exponential growth model equally well. Although, power growth model is indicated for four data sets, by the two growth rate function methodology, it was logistic or exponential model found fit to explain growth of those data sets as well. Therefore, results in this study emphasises the need to undertake more such studies on the time series data on publications growth of various fields to test the utility of two growth rate functions methodology.